2010
DOI: 10.1128/cvi.00494-09
|View full text |Cite
|
Sign up to set email alerts
|

Interactive Changes between Macrophages and Adipocytes

Abstract: Obesity is associated with a proinflammatory state, with macrophage infiltration into adipose tissue. We tested the hypothesis that communication between macrophages and adipocytes affects insulin resistance by disrupting insulin-stimulated glucose transport, adipocyte differentiation, and macrophage function. To test this hypothesis, we cocultured 3T3-L1 adipocytes with C2D macrophages or primary peritoneal mouse macrophages and examined the impacts of macrophages and adipocytes on each other. Adipocytes and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
52
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(58 citation statements)
references
References 51 publications
(35 reference statements)
3
52
0
1
Order By: Relevance
“…Obesity results in recruitment of M1 macrophages to adipose tissues, and also triggers M2 to M1 adipose-resident macrophage conversion (Lumeng et al 2007(Lumeng et al , 2008, with higher levels of secreted activin A in M1 than in M2 macrophages (Sierra-Filardi et al 2011). Proinflammatory cytokines secreted by macrophages inhibit differentiation of preadipocytes (Lacasa et al 2007;Xie et al 2010). Activin A inhibits adipocyte differentiation in human and mouse cells (Hirai et al 2005;Zaragosi et al 2010), and human preadipocytes cultured in conditioned media from adipose-resident macrophages show increased Inhba mRNA expression (Zaragosi et al 2010).…”
Section: Adipose Tissue Inflammation and Metabolismmentioning
confidence: 96%
“…Obesity results in recruitment of M1 macrophages to adipose tissues, and also triggers M2 to M1 adipose-resident macrophage conversion (Lumeng et al 2007(Lumeng et al , 2008, with higher levels of secreted activin A in M1 than in M2 macrophages (Sierra-Filardi et al 2011). Proinflammatory cytokines secreted by macrophages inhibit differentiation of preadipocytes (Lacasa et al 2007;Xie et al 2010). Activin A inhibits adipocyte differentiation in human and mouse cells (Hirai et al 2005;Zaragosi et al 2010), and human preadipocytes cultured in conditioned media from adipose-resident macrophages show increased Inhba mRNA expression (Zaragosi et al 2010).…”
Section: Adipose Tissue Inflammation and Metabolismmentioning
confidence: 96%
“…Obesity is associated with low-grade systemic inflammation and increased levels of pro-inflammatory cytokines such as IL-6 and TNF-α [2]. These cytokines are produced from adipocytes and ATM, contributing to insulin resistance [35,36]. Thus, we examined whether rAd-GLP-1-treatment reduces macrophage infiltration and pro-inflammatory cytokine production in adipose tissue.…”
Section: Discussionmentioning
confidence: 99%
“…Previous work by Ruan et al has shown that the primary adipocyte isolation process itself induces an infl ammatory response as measured by secretion of TNF-␣ and IL-6, which have been shown to have insulin-desensitizing effects (14)(15)(16)(17)(18)(19)24 ). This prior study additionally demonstrated that the isolation process leads to the downregulation of several genes involved in insulin signaling.…”
Section: Effects Of Collagenase Concentration and Rotational Speed Onmentioning
confidence: 48%
“…2D ). Importantly, the concentrations of IL-6 secreted from adipocytes isolated by rotating at 30 and 75 rpm ( ‫ف‬ 2,500 pg/ml and ‫ف‬ 1,500 pg/ml, respectively) approach the concentrations reported to reduce insulin sensitivity in adipocytes (5,000-20,000 pg/ml) ( 16,19 ).…”
Section: P38 Mapk Activation and Il-6 Secretion Are Attenuated In Rapmentioning
confidence: 99%
See 1 more Smart Citation